2021
DOI: 10.1177/1077801220978802
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Religion and Modernization on Egyptian Women’s IPV Attitudes

Abstract: This article uses the 2008 Egypt Demographic and Health Survey to explore the relationship between religion and women’s attitudes toward intimate partner violence (IPV). It also asks whether modernization, as measured by having a higher education or living in an urban area, can mediate or moderate this relationship. Using latent class analysis to create categories of women’s wife-beating attitudes, and multinomial regression to explore the relationship between religion, education, and urbanity, we find no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…Jung and Olson (2017) indicated that such findings might be related to the underrepresentation of Muslims in their sample. Golriz and Miner (2021) also found that in Egypt, being a Muslim is not significantly related to an individual's attitude toward wife beating. However, Golriz and Miner's (2021) sample was highly skewed, and 95% of their sample was Muslim.…”
Section: Country-level Factorsmentioning
confidence: 90%
See 1 more Smart Citation
“…Jung and Olson (2017) indicated that such findings might be related to the underrepresentation of Muslims in their sample. Golriz and Miner (2021) also found that in Egypt, being a Muslim is not significantly related to an individual's attitude toward wife beating. However, Golriz and Miner's (2021) sample was highly skewed, and 95% of their sample was Muslim.…”
Section: Country-level Factorsmentioning
confidence: 90%
“…Golriz and Miner (2021) also found that in Egypt, being a Muslim is not significantly related to an individual's attitude toward wife beating. However, Golriz and Miner's (2021) sample was highly skewed, and 95% of their sample was Muslim. The finding from such a skewed distribution of religions among populations is questionable.…”
Section: Country-level Factorsmentioning
confidence: 90%
“…Critics of this approach argue that apart from arrogance, this perception represents a poor understanding of historical and ideological contexts and especially the role of poverty and global inequality for women in Muslim countries (Abu-Lughod, 2013; Golriz and Miner, 2021). For example, with all to do with the women situation in Afghanistan, Abu-Lughod is not denying the oppression they faced.…”
Section: Literature Reviewmentioning
confidence: 99%